The Barque of Wenut-Shemau at the Sed-Festival: An Old Kingdom Temple Relief from Herakleopolis - Wegner, Josef.
In the collection of the University of Pennsylvania Museum is a limestone relief depicting a king at life-size engaged in a boat ritual as part of the Sed-festival. Discovered in 1904 at Herakleopolis, this object can be dated, based on context, iconography, and style to the early Old Kingdom. Only the upper part of this monumental relief is preserved and the name of the king does not survive. However, the associated labels show that the scene depicted a king, accompanied by Iunmutef, receiving the barque of the goddess Wenut-Shemau, or Nekhbet, at the Sed-festival. This relief, reused in the foundations of the Twelfth Dynasty at Herakleopolis derives from what was evidently a large-format tableau of Sed-festival scenes in a royal cult complex of the Old Kingdom. The relief is a forerunner to scenes in the Twentieth Dynasty tomb of Setau at El Kab depicting the arrival of Wenut-Shemau at the site of the Sed-festival. The ceremonial mooring of the barques of Wadjet and Nekhbet at the Sed-festival may form a central, but hitherto unrecognized, element of the Sed-festival. The closest surviving parallels to the Herakleopolis scene occur in fragmentary reliefs from the Valley Temple of Sneferu at Dahshur. Attribution is proposed to Huni, Sneferu or Khufu. The Sed-festival block may have been transported to Herakelopolis from one of the Memphite pyramid complexes, or from Meidum, during the early Twelfth Dynasty. Alternatively, the relief may derive from an early Old Kingdom royal complex at Herakelopolis itself, possibly originating in a mortuary complex of Huni that once stood at that site.  doi: http://dx.doi.org/10.5913/jarce.53.2017.a007